1995
DOI: 10.1073/pnas.92.18.8274
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde axonal transport of glial cell line-derived neurotrophic factor in the adult nigrostriatal system suggests a trophic role in the adult.

Abstract: The recently cloned, distant member of the transforming growth factor 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
157
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(171 citation statements)
references
References 29 publications
12
157
2
Order By: Relevance
“…The receptor for GDNF, GDNF receptor ␣1 (GFR␣1), and its signaling tyrosine kinase, Ret, are both highly expressed in SNpc during development (Widenfalk et al, 1997;Yu et al, 1998). As expected for a target-derived factor, GDNF can be specifically transported retrograde from striatum to SNpc (Tomac et al, 1995b). We showed that GDNF uniquely suppressed apoptosis specifically within DA neurons in a primary postnatal culture model established during the first phase of natural cell death (Burke et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…The receptor for GDNF, GDNF receptor ␣1 (GFR␣1), and its signaling tyrosine kinase, Ret, are both highly expressed in SNpc during development (Widenfalk et al, 1997;Yu et al, 1998). As expected for a target-derived factor, GDNF can be specifically transported retrograde from striatum to SNpc (Tomac et al, 1995b). We showed that GDNF uniquely suppressed apoptosis specifically within DA neurons in a primary postnatal culture model established during the first phase of natural cell death (Burke et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…This DA cell protection in the SN may be owing to the GDNF produced and released in the striatum (B1300 pg/ striatum corresponding to B0.06 ng/mg of tissue), which is then retrogradely transported to the SN where it initially enhances the resistance of DA neurons to the 6-OHDA lesion. The retrograde transport of GDNF from the striatum to the SN has been demonstrated by Tomac et al 31 The effect of GDNF may also result from the retrograde transport of the vector itself from the striatum to the SN where it can produce neurotrophic factor. The retrograde transport of Ad vectors from the striatum to the SN has been reported by Byrnes et al 32 In our study, the levels of GDNF measured in the striatum were sufficient to protect DA neurons from the 6-OHDA lesion although they were lower than levels observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was possibly because of retrograde delivery from striatal dopaminergic nerve terminals to the cell bodies in the SNpc (Tomac et al, 1995) and anterograde axonal transport from striatal neurons to the afferent regions via the indirect pathway, plus axonal sprouting between the two striatal hemispheres (Ciesielska et al, 2011;Richardson et al, 2011). These off-target effects may provide some advantages in GDNF application for PD treatment, but levels of GDNF transported indirectly to these afferent regions are unpredictable, particularly when higher vector doses or longer expression times are required (Bartus et al, 2011;Drinkut et al, 2012).…”
Section: Discussionmentioning
confidence: 99%